(untitled) (Third Sector Social Economic Review, 2022)
With globalization and the spread of mass media, today’s businesses are getting easier to enter international markets, and it is getting harder and harder to maintain their continuity in international markets due to the increase in competition. In this perspective, the possible serious effects on the export performance of the enterprises and the choice of entry into international markets and adaptation strategies become even more critical. The main purpose of this study is to determine the regulatory role of market entry strategies in the effect of adaptation strategies applied in international markets on export performance. Data were collected by using the hypotheses created in line with the purpose of the study, the scales with proven validity and reliability, and a survey study applied to 400 enterprises with convenience sampling from 950 carpet enterprises operating in Gaziantep and registered to the Southeastern Anatolia Exporters’ Association. As a result of the analysis, positive relationship between export performance and product adaptation; a medium level positive relationship between price adaptation; a very strong positive relationship between promotion adaptation; It was determined that there was a positive medium level relationship between distribution adaptation. At the same time, it has been determined that entry strategies have a moderating role in the effect of price adaptation on export performance, while entry strategies do not have a regulatory role in the effect of product, promotion and distribution adaptation on export performance.